Celestial Beliefs and Religions in the Poem of Veteran Poets - Al-Nuaimi, Thawiba Ahmed Dayeh Hassan; Rashed, Ansam Mohammed (Al-Adab Journal, 2022)
If we want to enter the pre-Islamic life and know its beliefs and religions that prevailed in that era that was called the era of the period, that is, the era between two messengers, we must first refer to the Holy Qur’an, as it has rejected many of the customs and traditions that prevailed during the days of ignorance, and this is what he indicated Dr. Taha Hussein said: “In studying pre-Islamic poetry I have taken two paths, one that has no doubt about its validity, which is the Holy Qur’an. The Qur’an is the truest mirror of the pre-Islamic era. Those who contemplated and debated the prophet, and they are the veterans".